2016
DOI: 10.1371/journal.pone.0166029
|View full text |Cite
|
Sign up to set email alerts
|

Highly Connected Populations and Temporal Stability in Allelic Frequencies of a Harvested Crab from the Southern Pacific Coast

Abstract: For marine invertebrates with a benthic adult form and a planktonic larva phase, the connectivity among populations is mainly based on larval dispersal. While an extended larval phase will promote gene flow, other factors such as an intensive fishery and geographical barriers could lead to changes in genetic variability. In this study, the population genetic structure of the commercial crab Metacarcinus edwardsii was analyzed along 700 km of the Chilean coast. The analysis, based on eight microsatellite loci g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…The analyses did not detect population differentiation, except for slight but significant differences in F ST when pairs of sites with small sample sizes were compared. This temporal stability has been previously described for this species; Rojas-Hernández et al 36 did not detect differences in microsatellite variability in four cohorts of megalopas (over the period 2011 to 2014) collected at Los Molinos (39° 51′ S; 73° 23′ W). To our knowledge, there is little evidence of the temporal genetic stability of populations of benthic marine organisms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The analyses did not detect population differentiation, except for slight but significant differences in F ST when pairs of sites with small sample sizes were compared. This temporal stability has been previously described for this species; Rojas-Hernández et al 36 did not detect differences in microsatellite variability in four cohorts of megalopas (over the period 2011 to 2014) collected at Los Molinos (39° 51′ S; 73° 23′ W). To our knowledge, there is little evidence of the temporal genetic stability of populations of benthic marine organisms.…”
Section: Discussionsupporting
confidence: 82%
“…Larvae recruit in association with the estuarine environment 34 . Laboratory experiments have demonstrated a planktonic larval duration of 60 days at 15 °C 35 , and a population genetic study based on eight microsatellites found high gene flow among populations over 700 km apart 36 . However, the possible effect of the Humboldt Current on gene flow, temporal genetic stability, and population differentiation of the species across the biogeographic break at 42°S remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been given to the biogeographic break located at 30°S that separates the Peruvian province from the intermediate area. This break is the distributional boundary for many species (both equatorward and poleward) and has been documented as an effective barrier to gene flow for some species that have distributions that cross this break (for examples see Haye et al, 2014Haye et al, , 2019Montecinos et al, 2012;Tellier et al, 2009) but not for others (such as in Cárdenas et al, 2009;Rojas-Hernandez et al, 2016). In addition, long-term surveys have shown that environmental characteristics, particularly upwelling, not only are highly heterogeneous along the Chilean Pacific coast but also change dramatically across the 30°S latitude (Aravena et al, 2014;Broitman et al, 2018;Lara et al, 2019;Torres et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This iteroparous, partial spawner has a pelagic larval life span of 30-45 days, similar to other benthic marine organisms (Chong and González, 2009;Marshall and Morgan, 2011;Toledo et al, 2017). The pelagic larvae are expected to be distributed by ocean currents over wide geographic areas, contributing to panmixia (Cowen et al, 2007;Rojas-Hernandez et al, 2016). Thus, this fish is thought to have limited genetic structure due to the lack of oceanographic barriers, which promotes connectivity.…”
Section: Introductionmentioning
confidence: 99%